2021
DOI: 10.3390/jcm10204750
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Uric Acid in Acute and Chronic Coronary Syndromes

Abstract: Uric acid (UA) is the final product of the catabolism of endogenous and exogenous purine nucleotides. While its association with articular gout and kidney disease has been known for a long time, new data have demonstrated that UA is also related to cardiovascular (CV) diseases. UA has been identified as a significant determinant of many different outcomes, such as all-cause and CV mortality, and also of CV events (mainly Acute Coronary Syndromes (ACS) and even strokes). Furthermore, UA has been related to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
25
1
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 75 publications
0
25
1
1
Order By: Relevance
“…Uric acid (UA) is the final degradation product of purine nucleotides from endogenous (cellular nucleoproteins) and exogenous origins (alimentary) [ 192 ]. In the Framingham study that included 5127 participants followed up for 12 years, Kannel et al established the link between UA and CV events by demonstrating an elevated risk of myocardial infarction in people with hyperuricemia [ 193 ].…”
Section: Resultsmentioning
confidence: 99%
“…Uric acid (UA) is the final degradation product of purine nucleotides from endogenous (cellular nucleoproteins) and exogenous origins (alimentary) [ 192 ]. In the Framingham study that included 5127 participants followed up for 12 years, Kannel et al established the link between UA and CV events by demonstrating an elevated risk of myocardial infarction in people with hyperuricemia [ 193 ].…”
Section: Resultsmentioning
confidence: 99%
“… 1 A study conducted in Adelaide showed that the prevalence of hyperuricaemia in South Australia is relatively high, with an overall prevalence of 16.6%. 2 Several epidemiological studies indicated that serum uric acids (SUA) had a detrimental effect on the prevalence of metabolic diseases, such as cardiovascular diseases, 3 metabolic syndrome. 4–6 Recent study found that serum gamma-glutamyl transferase (GGT) concentration were strongly related to elevated uric acid level in normotensive adults.…”
Section: Introductionmentioning
confidence: 99%
“…Uric acid (UA) is the final product of the purine catabolism (6). While UA has been linked to kidney illness and articular gout, recent research has shown that it could also be connected to cardiovascular (CV) disorders (6,7,8). It also has some connection with metabolic disorders such as diabetes mellitus.…”
Section: Introductionmentioning
confidence: 99%